Peningkatan kemampuan pemecahan masalah matematis siswa kelas VII melalui penerapan model pembelajaran creative problem solving (CPS) berbasis kontekstual - Herlawan Herlawan; Hadija Hadija (Program Studi Pendidikan Matematika, FKIP, Universitas Siliwangi, Tasikmalaya, 2017)
The purpose of this research is to know about the improvement of the mathematical problem-solving ability of grade VII students through the application of creative problem-solving model based on contextual. This study included quasi-experimental. The population involves all students of class VII SMPN 2 Lapandewa consisting of three classes and samples taken by purposive sampling so selected 25 students from class VIIA as an experimental class and 25 students of class VIIC as a control class. The research instruments are pretest and postes problem-solving abilities. The data of the research were analysed using independent samples t-test. The result of the research shows that the improvement of mathematical problem-solving ability of students who follow creative problem solving based on contextual learning is better than who follow conventional learning. Thus this model can be used as an alternative effective learning model to improve students’ mathematical problem-solving skills optimally, especially on the rectangular material.